TAX AVOIDANCE, CORPORATE GOVERNANCE AND FINANCIAL PERFORMANCE OF COMPANIES REGISTERED IN THE JAKARTA ISLAMIC INDEX - Jati, Ahmad Waluya; Ulum, Ihyaul; Utomo, Cahyo (Universitas Muhammadiyah Malang)
ax aTax avoidance is a tax savings actions that are still in the realm of tax law (lawful fashion). Financial performance and corporate governance are used as independent variables were estimated impact on tax avoidance as the dependent variable. Financial performance indicators are ROA, DAR, and DPR. Corporate governance is proxied with the percentage of attendance of the board of directors, board of commissioners and audit committee, the proportion of independent commissioners, and managerial ownership. Tax avoidance as a dependent variable is measured by effective tax rate (ETR). This research was conducted on companies incorporated in the Jakartaâ€™s Islamic Index 2016. The samples in this study used nonprobability sampling method with purposive sampling technique in order to get a sample size of 26 companies. Data in this study were analyzed with SEM-PLS. The results of this study indicate that the financial performance and corporate governance has an effect on tax avoidance.Â